Discrecionalidad vs Seguridad Jurídica: Un estudio de la sanción disciplinaria de suspensión de funciones en la Policía Nacional Ecuatoriana - Inga Llumiugsi, Stalin David (2024)
This study is entitled “Discretionality vs. Legal Security: A study of the Disciplinary Sanction of Suspension of Duties in the Ecuadorian National Police”. It is placed in a context of essential legal principles such as the principle of legality together with those of legal security and legitimate confidence, established in the Organic Code of Citizen Security and Public Order Entities (COESCOP, 2017). These principles are vital to ensure legality and the protection of the rights of civil servants. To achieve this goal, the objective is to analyze the relationship between administrative discretion and legal security in the specific context of the disciplinary sanction of suspension of duties as a sanctioning measure in serious misconduct within the Ecuadorian National Police and its civil servants. This objective was achieved thanks to the effective application of the methodology and its research instruments. The results and discussion were essential to evaluate how disciplinary sanctions are managed, which have a significant impact on the morale and effectiveness of the police force, thus establishing clear and fair policies that promote a positive work environment and respect for internal rules and authorities. Furthermore, it was possible to evaluate whether the current procedures for suspension of duties are adequate and respect the legally established rights, allowing to make assertive and fair decisions. It is concluded that the correct implementation of these principles is key for administrative decisions to be timely, clear, and predictable. The research provides legal information that ensures effective protection of individual rights, avoiding the violation of rights of the police force, focused on due process and equality before the law, which in turn will strengthen the legitimacy of the police by identifying areas for improvement in their disciplinary practices, promoting transparency and accountability.